Profil Miskonsepsi Peserta Didik SMP/MTs di Kecamatan Lubuk Kilangan Menggunakan Intrumen Four-Tier Test - Nazwa Syahlilla Sudirman; Arif, Khairil; Lestari, Tuti; Putri, Rahmah Evita (SEMESTA: Journal of Science Education and Teaching, 2026)
Science education covers material related to the natural world, which consists of various scientific concepts that have been agreed upon by experts. If the diversity of concepts studied by students is not managed and directed appropriately by teachers, this has the potential to cause errors in understanding the correct concepts. To measure the level of students' understanding of concepts after studying a subject, teachers need to identify that understanding. This study aims to analyze students' misconceptions about vibration, waves, and light. The research method used is descriptive with a quantitative approach. The research population consists of 9th grade students in junior high school. The sampling technique used was cluster sampling with the criteria of public schools, accredited A, and the same teacher in each school; based on these criteria, the research sample consisted of 85 students. The research data was collected through 17 items of the Four-Level Test, which consisted of four levels: multiple-choice questions, confidence in answers, reasons for answers, and confidence in reasons for answers. The average misunderstanding experienced by students based on the learning objectives in the material on vibrations, waves, and light was classified as low, namely 8%. The highest misconception was found in the learning objective of applying the concept of vibration in everyday life, which was 47%. The lowest percentage of misconception, 14%, was found in the learning objective of classifying examples of waves. The results of this study can be used as a basis for educators to design learning that emphasizes strengthening conceptual understanding and clarifying misconceptions in the material on vibrations, waves, and light.